Incidence, Treatment, and Outcomes of Childhood Cancers in Calabar, Nigeria: A 10-year Review - Anthony Chibueze Nlemadim; Kingsley Onorhide Akaba; Ima-Obong Asuquo Ekanem; Roseline Ekanem Duke; Elizabeth Dennis Nkanga; Theophilus Ipeh Ugbem; Gabriel Unimke Udie; Ekaete Joseph Asuquo; Jacinta Banku Okoi-Obuli; Anthonia Asanye Ikpeme; Friday Akwagiobe Odey; Martin Madu Meremikwu (Nigerian Journal of Medicine, 2024)
Introduction: Cancers invade and destroy various parts of the body leading to death, if untreated. The burden of pediatric cancer is rising, especially in resource-poor regions. The aim of the study was to determine the incidence of childhood cancer types, basis of diagnosis, therapy received, and outcomes. Materials and Methods: This was a retrospective study of children aged 0-17 who were diagnosed and treated for cancer from January 2013 to December 2022. Data obtained included biodata, diagnoses, initial disease stage, diagnostic investigation results and treatments from medical records. Other outcomes assessed were relapse, abandonment of therapy, and death. Results: Of the 229 patients, males were 57.6%, 51.5% were in age-group 0-4 years and mean(SD) annual cancer crude incidence rate (CIR) was 0.29(0.09)/100,000 children. Retinoblastoma increased from 0.16/100,000 children in 2013 to 0.27/100,000 children in 2022 and had the highest average age-standardized incidence rate (0.11/100,000 children). Other malignancies had annual CIR between 0.01 and 0.08/100,000 children. The most common method of diagnosis was primary site histology (39.7%). Majority had late-stage disease (66.4%), incomplete chemotherapy (62.5%), no surgery (54.5%), and no radiotherapy (99.1%). There was disease relapse (20.5%), treatment abandonment (42.8%), discharged against medical advice (23.6%) and death (29.7%). More males than females died (1.5:1). The crude mortality rate of retinoblastoma increased from 0.01 to 0.12/100,000 children, while others fluctuated between 0.01 and 0.04/100,000 children. The average age-standardized mortality rate was highest in 0–4 years’ age group (48.5%). Conclusion: The rate of new cancers, particularly retinoblastoma, is rising in our locality. Majority present in advanced disease and are not effectively treated, resulting in increasing mortality rates. Periodic audit of childhood cancer burden may help relevant stakeholders in determining ways of curbing these worsening pediatric cancer trends.